Calculation of Absorption Dose Value using MIRD Method with Cobalt 57 MIBI for Four Body Organs - Asep Yoyo Wardaya; Wahyu Setia Budi; Ali Khumaeni; Chorirul Anam; Gani Gunawan (Journal of Physics and Its Applications, 2019)
MIRD has developed methods, assumptions, models, and mathematical formulae for estimating internal radiation doses from the injected radiopharmaceuticals into the body. This study aims to determine the radiopharmaceutical distribution of Cobalt 57 MIBI in patients identified as having breast cancer by using an oncology examination with MIRD method on 4 patient's organs with some time variations. The four organs of the patient's body are the heart, thyroid, kidney, and liver. The MIRD method developed to calculate the absorption dose of each organ is the product of the cumulative activity and the S factor of each organ studied. The results showed that the highest uptake dose in these patients was in the thyroid and kidney organs, and then followed by the heart and liver. These results indicate that the thyroid and kidney organs are the most vulnerable organs by the method of injecting radiopharmaceutical doses into the body of breast cancer patients.